Does shadow economy matters for tourism? International evidence - Din, Badariah; Habibullah, Muzafar Shah; Abdul Hamid, Baharom (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Tourism has been an important sector by contributing government revenues, national income, foreign exchange earnings as well as provides job and business opportunities for many nations. In 2013, international tourist arrivals reached a record 1.1 billion arrivals worldwide, with USD1.2 billion in international tourism receipts. At the same time,the shadow economy in the tourism sector also flourishes. In the European countries, Schneider reported that 20 to 25 percent of the shadow economy is represented in the tourism-related industries – wholesale and retail, automotive and motorcycle sales and maintenance; transportation, storage and communications; and hotels and restaurants. Services given by these operators (unregistered and/or underreporting) will ultimately wiped off the map of high quality tourist destinations and destroyed the development of the tourism industry itself. This study examines the short-run and long-run dynamics between international tourists’ arrival and shadow economy for 141 countries over the period 1995-2008. We use an error-correction model (ECM) in combination with a system Generalized Method of Moments (GMM) to explore the long-run relationship between these two variables. Our results suggest that tourists’ arrival and shadow economy are cointegrated. The long-run coefficients indicate a negative impact of the shadow economy on the tourism sector. This implies that shadow economy matters for the tourism industry worldwide.